Enterprise Potential: Essence, Classification and Types - Turylo Anatolii M.; Bohachevska Kateryna V. (Bìznes Inform, 2014)
The article considers existing approaches to classification of the enterprise potential as an economic notion. It offers own vision of classification of enterprise potential, which meets modern tendencies of enterprise development. Classification ensures a possibility of a wider description and assessment of enterprise potential and also allows identification of its most significant characteristics. Classification of the enterprise potential is developed by different criteria: by functions, by resource support, by ability to adapt, by the level of detection, by the spectrum of taking into account possibilities, by the period of coverage of possibilities and by the level of use. Analysis of components of the enterprise potential allows obtaining a complete and trustworthy assessment of the state of an enterprise. Adaptation potential of an enterprise is based on principles systemacy and dynamism, it characterises possibilities of adjustment of an enterprise to external and internal economic conditions.